THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN PRINCIPAL LEADERSHIP: A SYSTEMATIC LITERATURE REVIEW OF TRENDS, TOOLS, AND IMPACTS - Prasad, Anjana; Sahu, Manju (International Journal of Engineering Technologies and Management Research, 2025)
As schools move further into the digital age, Artificial Intelligence (AI) is starting to play a growing role in how principals lead and make decisions. This systematic literature review explores how AI is being integrated into school leadership, focusing on the trends, tools, and impacts reported in peer-reviewed studies published between 2010 and 2025. Using the PRISMA method, we reviewed research from sources like Scopus, Google Scholar, and Dimensions to understand how AI is changing the responsibilities of school leaders. The findings show that AI is helping principals in several key areas: automating routine tasks, using data to make better decisions, supporting teachers, and creating more personalized learning environments for students. Digital Tools like smartboards, projectors and dashboards are becoming more common in schools. At the same time, challenges such as lack of training, concerns about data privacy, and ethical use of AI are also highlighted. Overall, the study shows that while AI offers many opportunities to support effective school leadership, there is a clear need for professional development, thoughtful policies, and further research. By understanding how AI is currently being used, this review helps educators, policymakers, and developers move toward smarter and more responsible use of technology in schools.